Effects of beach slope breaks on nearshore groundwater dynamics. Issue 14 (1st June 2017) - Zhang, Ying; Li, Ling; Erler, Dirk V.; Santos, Isaac; Lockington, David
Abstract: Interactions between fresh groundwater and seawater affect significantly the nearshore pore water flow, which in turn influences the fate of nutrients and contaminants in coastal aquifers prior to discharge to the marine environment. Field investigations and numerical simulations were carried out to examine the groundwater dynamics in the intertidal zone of a carbonate sandy aquifer on the tropical island of Rarotonga, Cook Islands. The study site was featured by distinct cross‐shore slope breaks on the beach surface. Measured pore water salinities revealed different distributions under the influences of different beach profiles, inland heads, and tidal oscillations. Fresh groundwater was found to discharge around a beach slope break located in the middle area of the intertidal zone. The results indicate a strong interplay between the slope break beach morphology and tidal force in controlling the nearshore groundwater flow and solute transport. The fresh groundwater discharge location was largely determined by the beach morphology in combination with the tidal force. The nearshore groundwater flow can be very sensitive to beach slope breaks, which induce local circulation and flow instabilities. As slope breaks are a common feature of beaches around the world, these results have important, general implications for future studies of nutrients transport and transformations in nearshore aquifers and associated fluxes via submarine groundwater discharge.